Clinical Profile of Dengue Patients who had a Prior Infection with the Covid 19 Virus in a Tertiary Care Centre - Jyoti Prakash (Recent Trends in Infectious Diseases, 2023)
This cross-sectional analytical study conducted in a tertiary care center aims to investigate the clinical profile of Dengue virus-infected patients with a prior history of COVID-19 within the last three years. Dengue, a prevalent tropical disease, ranges from mild fever to severe conditions like hemorrhagic fever and shock syndrome. The study utilizes the World Health Organization's 2009 classification for Dengue and delineates the febrile, critical, and recovery phases of infection. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causing COVID-19, has become a global pandemic with significant respiratory, cardiovascular, gastrointestinal, and neurological impacts. The research question focuses on comparing clinical parameters of Dengue patients at AIIMS Patna based on their history of prior COVID-19 infection. The primary objective is to study and compare the clinical profiles, with secondary objectives exploring the roles of age and gender in prognosis and outcomes. The study, conducted from September to November 2023, is novel in predicting Dengue severity in previously COVID-19-infected patients in Bihar. The sampling involves Dengue-positive patients admitted to the Medicine Ward using non-randomized convenience purposive sampling. The inclusion criteria encompass age ≥ 18, positive Dengue markers, and admission during the study period. The study excludes equivocal or negative Dengue cases and those without informed consent. Data collection involves comprehensive clinical assessments and laboratory tests, with statistical analysis planned using appropriate tests and applications. This research contributes valuable insights into the interaction of Dengue and prior COVID-19 infections in a region with limited previous studies on this subject.
Keywords: 1. Dengue 2. Covid-19 3. Dengue IgM 4. Dengue NS1 Ag 5. COVID DENGUE